Gene therapy for hearing loss - Omichi, Ryotaro; Shibata, Seiji B; Morton, Cynthia C; Smith, Richard J H (Human molecular genetics, 2019)
Abstract Sensorineural hearing loss (SNHL) is the most common sensory disorder. Its underlying etiologies include a broad spectrum of genetic and environmental factors that can lead to hearing loss that is congenital or late onset, stable or progressive, drug related, noise induced, age related, traumatic or post-infectious. Habilitation options typically focus on amplification using wearable or implantable devices; however exciting new gene-therapy-based strategies to restore and prevent SNHL are actively under investigation. Recent proof-of-principle studies demonstrate the potential therapeutic potential of molecular agents delivered to the inner ear to ameliorate different types of SNHL. Correcting or preventing underlying genetic forms of hearing loss is poised to become a reality. Herein, we review molecular therapies for hearing loss such as gene replacement, antisense oligonucleotides, RNA interference and CRISPR-based gene editing. We discuss delivery methods, techniques and viral vectors employed for inner ear gene therapy and the advancements in this field that are paving the way for basic science research discoveries to transition to clinical trials.